Reliability of Youth's Responses on Their Status Projections A Test-Retest Evaluation in Depth - Kuvlesky, William P.; Lever, Michael F.; Texas A and M Univ., College Station. Texas Agricultural Experiment Station ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The status projections of high school sophomores residing in rural East Texas were surveyed in spring of 1972. Focus was on their aspirations and expectations for status attainment in occupation, education, income, and type of place of residence. In each area, four elements of status projections were examined: aspiration level, expectation level, certainty of expectation, and intensity of aspiration. A small-scale investigation of the observations made in the initial study was later conducted with 11 respondents from a school where the interview situation had been far from ideal. This study evaluated observation reliability, in terms of consistency of responses, through a "test-retest" procedure over a 2-week time lapse. Data were collected via the same group-administered questionnaire used in the initial study. Among the findings were: (1) variation in response, in terms of initial coded measurements, was relatively high across all status areas, except for status object of aspirations; and (2) generally, indicators for all elements of educational status projections were more stable than those of other status areas. The general intent of this study was to produce some reasonable hypotheses for additional and broader research since the limited sample does not allow for generalizations. (NQ)
Sponsoring Agency: Cooperative State Research Service (USDA), Washington, DC.
ERIC Note: Paper presented at the Annual Meeting of the Rural Sociology Section, Southern Association of Agricultural Scientists (New Orleans, Louisiana, February 1975).
Educational level discussed: Grade 10.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Aspiration; Aspiration; Evaluation Criteria; Expectation; Grade 10.; High School Students; Occupational Aspiration; Reliability; Rural Youth; Socioeconomic Status; Status; Reports, Research